AKTOR CZY ZWYKŁY CZŁOWIEK? BOHATER TELEWIZYJNYCH REALITY SHOWS - Sosnowska, Joanna (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The article is an image analysis of ordinary people in television entertainment. Television image ordinary the man is in our times particularly interesting in reality show. Programs reality show are showing the wide image of all sorts social groups: of the wife, the mother or teenagers. It turns out that however it isn’t image of the ordinary man. Everyone must be exceptional: mother - lonely, wife - obese, and teenager - talented. In our times everyone can become a television star through reality show.